Utilization of Eggshell By-Products For Calcium Fortification in Various Food Products: Literature Review - Suci Apsari Pebrianti; Fikri Muhamad Ilyas (Journal of Food and Agricultural Product, 2024)
The level of production and consumption of chicken eggs in Indonesia continues to increase. This condition will be in line with the amount of eggshell waste that has not been utilized properly. Egg shells are rich in calcium and have the potential to be used as a calcium source in the form of powder or flour through fortification into various foods. As for right now, there is no literature study available that addresses the impact of eggshell powder addition as a calcium fortification affects the characteristics and level of acceptance of various food products This literature review used the scoping review method, and the articles used in this review were obtained through searches using Google Scholar, ResearchGate, and PubMed. The results of this literature review show that eggshell powder is suitable to be added to food products as a source of calcium. Adding eggshell powder can greatly increase the calcium content of a variety of foods. Aroma, taste, and texture are the organoleptic characteristics that are mainly impacted by the addition of eggshell powder. The addition of eggshell powder is generally contradictory to the degree of liking and acceptability of the product. The degree of product acceptance and liking tends to decrease as eggshell powder concentration increases. Thus, it is imperative to perform suitable calculations concerning the highest concentration of eggshell powder applied to preserve the food product's unique qualities and attributes while preventing a decline in the product's degree of acceptance or liking. Keywords: calcium, eggshell, fortification